PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN JEMAAH UMRAH DI PT. QIBLATAIN SAFARINA BAKTI - Nur Putriani, Erin (JSE: Jurnal Sharia Economica, 2026)
This study aims to analyze the influence of service quality and trust on the satisfaction of Umrah pilgrims at PT. Qiblatain Safarina Bakti. The study used a quantitative approach with a survey technique. The study population was Umrah pilgrims who used the services of PT. Qiblatain Safarina Bakti, with a sample of 85 respondents taken using a saturated sampling technique. Data were collected through a questionnaire with a Likert Scale and analyzed using IBM SPSS multiple linear regression analysis. The results showed that service quality had a positive and significant effect on pilgrim satisfaction (t value = 6.148; sig. = 0.000), trust had a positive and significant effect (t value = 5.560; sig. = 0.000), and both variables simultaneously had a significant effect (F value = 38.658; sig. = 0.000). The coefficient of determination (R²) showed that service quality and trust were able to explain variations in pilgrim satisfaction substantially. This finding strengthens the importance of the SERVQUAL and trust dimensions in the context of religious tourism services.